Amplitude Spectrum Area to Guide Defibrillation: A Validation on 1617 Patients With Ventricular Fibrillation. Issue 5 (3rd February 2015) - Ristagno, Giuseppe; Mauri, Tommaso; Cesana, Giancarlo; Li, Yongqin; Finzi, Andrea; Fumagalli, Francesca; Rossi, Gianpiera; Grieco, Niccolò; Migliori, Maurizio; Andreassi, Aida; Latini, Roberto; Fornari, Carla; et al.
Abstract : Background—: This study sought to validate the ability of amplitude spectrum area (AMSA) to predict defibrillation success and long-term survival in a large population of out-of-hospital cardiac arrests. Methods and Results—: ECGs recorded by automated external defibrillators from different manufacturers were obtained from patients with cardiac arrests occurring in 8 city areas. A database, including 2447 defibrillations from 1050 patients, was used as the derivation group, and an additional database, including 1381 defibrillations from 567 patients, served as validation. A 2-second ECG window before defibrillation was analyzed, and AMSA was calculated. Univariable and multivariable regression analyses and area under the receiver operating characteristic curve were used for associations between AMSA and study end points: defibrillation success, sustained return of spontaneous circulation, and long-term survival. Among the 2447 defibrillations of the derivation database, 26.2% were successful. AMSA was significantly higher before a successful defibrillation than a failing one (13±5 versus 6.8±3.5 mV-Hz) and was an independent predictor of defibrillation success (odds ratio, 1.33; 95% confidence interval, 1.20–1.37) and sustained return of spontaneous circulation (odds ratio, 1.22; 95% confidence interval, 1.17–1.26). Area under the receiver operating characteristic curve for defibrillation success prediction was 0.86 (95% confidence interval, 0.85–0.88). AMSA was also significantly associated with long-term survival. The following AMSA thresholds were identified: 15.5 mV-Hz for defibrillation success and 6.5 mV-Hz for defibrillation failure. In the validation database, AMSA ≥15.5 mV-Hz had a positive predictive value of 84%, whereas AMSA ⩽6.5 mV-Hz had a negative predictive value of 98%. Conclusions—: In this large derivation-validation study, AMSA was validated as an accurate predictor of defibrillation success. AMSA also appeared as a predictor of long-term survival. Abstract : Supplemental Digital Content is available in the text.